Pacoima Dam. - Gordon, John C. (photographer):::Creator::::::::::::
Photographs shows a portion of the Pacoima Dam with an aerial view of the Pacoima canyon and a housing development down below. Many homes in this area were condemned due to damage during the 1971 earthquake. Hazy features of photograph are dust clouds produced by landslides which continued for several days after the San Fernando, California earthquake.